2011
DOI: 10.1016/j.sna.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

An FPGA-based versatile development system for endoscopic capsule design optimization

Abstract: This work presents a development system, based on Field Programmable Gate Array (FPGA), that was specifically designed for testing the entire electronics to be integrated in an endoscopic capsule, such as a camera, an image compression engine, a high-speed telemetric system, illumination and inertial sensors. Thanks to its high flexibility, several features were tested and evaluated, thus allowing to find the optimal configuration, in terms of power consumption, performances and size, to be fit in a capsule. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The compressor system is implemented using a 0.18 µm CMOS process in 0.026 mm 2 of silicon area, and it achieved an 80% compression ratio while consuming 42 µW of power. The field-programmable gate array-based (FPGA-based) optimization of capsule design was proposed by Cavallotti et al [61]. According to their prototype ( Figure 6), it is possible to transmit a compressed image at the rate of 19 fps over a 1.5 Mbps channel.…”
Section: Research Progress For Next-generation Capsulesmentioning
confidence: 99%
“…The compressor system is implemented using a 0.18 µm CMOS process in 0.026 mm 2 of silicon area, and it achieved an 80% compression ratio while consuming 42 µW of power. The field-programmable gate array-based (FPGA-based) optimization of capsule design was proposed by Cavallotti et al [61]. According to their prototype ( Figure 6), it is possible to transmit a compressed image at the rate of 19 fps over a 1.5 Mbps channel.…”
Section: Research Progress For Next-generation Capsulesmentioning
confidence: 99%
“…Information on battery life was not found in their papers. The work in [6] reports 19 frames/s using an RF transceiver having a data rate of 1.5 Mbps. However, the transceiver was not interfaced with their prototype for real-time experimentation and such high frame rate will reduce the battery life of the system dramatically.…”
Section: Comparison With Other Workmentioning
confidence: 99%
“…The work in [6] presents a development system based on FPGA that was specifically designed for testing the entire electronics to be integrated in an endoscopic capsule. The implemented compressor is based on integer version of discrete cosine transform (DCT) and it needs the buffering of the entire image frame in an external SRAM which will consume a significant amount of silicon area and device power.…”
Section: Introductionmentioning
confidence: 99%
“…Taken altogether, these technologies allow clinicians to achieve imaging performances comparable with those offered by a flexible endoscope, even if power consumption and battery lifetime may still be a relevant downside for WCE, as better detailed in Section 3.4. A detailed description of the complete signal chain typical for a wireless capsule endoscope and the required electronic backbone was provided by Cavallotti et al (66), who demonstrated a real-time 19-fps video capsule.…”
Section: Image-based Sensing and Processingmentioning
confidence: 99%